Gamification Model Framework and its Use in E-Learning in Higher Education - Toimah, Tatu Fidiatu; Maulana, Yusril Ihza; Fajar, Irfan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2021)
The manuscript that we examined contains the introduction of gamification into e-learning lecture activities in universities. A literature study will explain conceptual differences between the techniques and methods of mechanics and game dynamics used by students. Gamification will be combined into e-learning at a university, and this has various benefits in the learning process, such as higher motivation, more fun learning, and active learning. This Paper shows the importance of gamification in learning, including in higher education. The manuscript that we created presents a different perspective on the concept of gamification in the University. The innovation in this paper describes incorporating characteristics of gamification and e-learning that can demonstrate the practical use of gamification in e-learning. The method used is a literature study. Further research expected that this framework can be applied in various universities.